Efficiency calibration and coincidence summing correction for a large volume (946 cm3) LaBr3(Ce) detector: GEANT4 simulations and experimental measurements. (December 2016) - Dhibar, M.; Mankad, D.; Mazumdar, I.; Kumar, G. Anil
Abstract: The paper describes the studies on efficiency calibration and coincidence summing correction for a 3.5″×6″ cylindrical LaBr3 (Ce)detector. GEANT4 simulations were made with point sources, namely, 60 Co, 94 Nb, 24 Na, 46 Sc and 22 Na. The simulated efficiencies, extracted using 60 Co, 94 Nb, 24 Na and 46 Sc that emit coincident gamma rays with same decay intensities, were corrected for coincidence summing by applying the method proposed by Vidmar et al. (2003). The method was applied, for the first time, for correcting the simulated efficiencies extracted using 22 Na that emits coincident gamma rays with different decay intensities. The measured results obtained using 60 Co and 22 Na were found to be in good agreement with simulated results. Graphical abstract: Highlights: Coincidence summing correction in a large LaBr3 (Ce) detector. Estimation of corrected absolute efficiencies by employing the method suggested byVidmar et al. (2003) Validation of the method for a positron emitter. The measured results obtained using 60 Co and 22 Na were found to be in good agreement with simulated results.